SIMPLE PRESENT TENSE VERB AND ADJECTIVES IN DESCRIPTIVE TEXT - Nurul Hikmah; Supeno Supeno (Universitas Indraprasta PGRI, 2020)
This objectives study are 1) to analyze and to know whether or not there are errors of simple present verb in students writing descriptive text; 2) to analyze and to know if there are errors of adjectives in students writing descriptive text; 3) to know the cause of errors simple present tense verb and adjectives in students writing descriptive text. The tenth-grade students at Islamic Centre high school and Nusantara 1 high school in Tangerang in the academic year 2019/2020 are the participants in this current research. The research is a case study and used a descriptive approach. The instrument of this study is the writing test. There were 30 writing had been analyzed. The results show the error of simple present verbs for errors omission (65,26%), addition (5,26%), selection (28,42%), misordering (1,05%). And errors in using adjective percentage: omission (13,95%), addition (0%), selection (76,34%), misordering (9,30%). The reasons for errors in simple present tense and adjectives in writing descriptive text made by students are interlingual and intralingual errors.